The antioxidant response mechanism of flavonoids in ‘Tainong 1’ mango pulp under enhanced UV-B radiation - Xian Shui; Tian-tian Chen; Min-jie Qian; Jun-jie Peng; Jing-jia Du; Kai-bing Zhou; Feng Liu (Cogent Food & Agriculture, 2024)
In this study, UV-B radiation of 96 kJ·m−2·d−1 exposed to the ‘Tainong 1’ mango tree, and trees as the control group under natural lighting. The relative conductivity and the contents of MDA, superoxide anion, H2O2 were lower in the treatment group than in the control group before 60 DAF, and the opposite occurred after 60 DAF. The total flavonoid content in the treatment group was higher than that in the control group, but the opposite occurred later. The 60 DAF serves as the critical point. Before 60 DAF, the treatment enhanced the activity of each enzyme by inducing the upregulated expression of genes such as CHS, R02446, and CYP98A so that gallochol, leucoside, kaempferoside, quercetin, isoquercetin and luteolin, and then removed ROS through the reduction of flavonoids. After 60 DAF, the treatment enhanced the activity of each enzyme by inducing the upregulated expression of HCT and R02446, but the synthesized flavonoids are consumed by ROS. Meanwhile, ROS also accumulate continuously because of the enhanced continuous exposure of UV-B radiation. The downregulated expression of CYP75A led to a decline in enzyme activity. The accumulation rate of flavonoid compounds was lower than that of ROS, which led to ROS damage in pulp.